Plasma Choline Concentration Was Not Increased After a 6-Month Egg Intervention in 6–9-Month-Old Malawian Children: Results from a Randomized Controlled Trial. Issue 2 (23rd February 2022) - Bragg, Megan G; Prado, Elizabeth L; Arnold, Charles D; Zyba, Sarah J; Maleta, Kenneth M; Caswell, Bess L; Bennett, Brian J; Iannotti, Lora L; Lutter, Chessa K; Stewart, Christine P
ABSTRACT: Background: Eggs are a rich source of choline, an essential nutrient important for child growth and development. In a randomized trial of 1 egg/d in young children in Ecuador, an egg intervention led to significant improvements in growth, which were partially mediated by increased plasma choline concentration. A similar trial in Malawi (clinicaltrials.gov : NCT03385252) found little improvement in child growth or development. Objectives: We aimed to evaluate the effect of 1 egg/d for 6 mo on plasma choline concentrations in Malawian children enrolled in a randomized trial. Methods: Infants aged 6–9 mo in rural Malawi were randomly assigned to receive 1 egg/d ( n  = 331) or serve as a nonintervention control ( n  = 329) for 6 mo. Anthropometric, developmental, and dietary data were collected at baseline and 6-mo follow-up, along with a blood draw. Plasma choline, betaine, dimethylglycine, trimethylamine N -oxide (TMAO), and DHA were measured at both time points using ultrahigh performance liquid chromatography–tandem MS ( n  = 200 per group). Linear regression analysis was used to determine the difference in plasma choline and related metabolites between groups after 6 mo of intervention. Results: Plasma choline, betaine, dimethylglycine, and DHA concentrations did not differ between groups at 6-mo follow-up. Plasma TMAO was significantly (26%; 95% CI: 7%, 48%) higher in the egg intervention group in a fully adjusted model. Conclusions: Provision of 1 egg/d for 6 mo did not result in increases in plasma choline or related metabolites, except TMAO. This could partially explain the lack of effect on growth and development. Additional interventions are needed to improve choline status, growth, and development in this population. Abstract : Provision of 1 egg/d for 6 mo did not result in increases in plasma choline or related metabolites, except TMAO, in this randomized trial of young Malawian children.